The Application of Social Control Theory in Preventing Violent Crime by Juvenile Delinquent - Widowaty, Yeni (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2019)
Yogyakarta has faced a number of violent crimes committed by a group of teenagers (juvenile delinquents). These include vandalism, destruction of public facilities and even murder. The purpose of the research was to find out factors that contribute to the rise of such crimes Yogyakarta and the possible solutions. This Socio-Legal research employed both primary and secondary data. It was found that factors causing violent crimes derived from both internal and external factors of the perpetrators. Both penal and non-penal policies have been taken to prevent the mentioned crime. The future concept is to approach violent crimes by juvenile delinquents through Social Control theory in the form of affection, trust, commitment, and involvement. The idea is to involve various parties in handling the problem. Not only police officers, other stakeholders such as parents, teachers, and religious leaders should also be involved.